THE IELTS READING TEST: A REVIEW ON ITS DEVELOPMENT AND LANGUAGE TEST PERFORMANCE - Masna, Yuliar (STKIP Bina Bangsa Getsempena Banda Aceh, 2016)
International English Language Testing System (IELTS) is regarded as one of proficiency tests that is generally accepted by British and Australian universities Â in selecting and screening Â overseas students. Changes in the tasks and texts of IELTS Reading test have been improved due to response to development in applied linguistics. In constructing the module of the IELTS reading test, there are several dimensions that should be considered by developers such as British Council; they are the validity, reliability, fairness, and impact of the test. This is very important in order that test takers can achieve more valid, reliable, and fair band scores from this section test. Therefore, this writing is aimed to review the development and language test performance of IELTS, particularly focusing on the IELTS Reading Test section.Â Keywords: proficiency test, validity, reliabilit